A comparative study of large-vessel and small-vessel primary angiitis of the central nervous system: insights from a Chinese single-center retrospective cohort - Wang, Yifan; Lyu, Jiangyi; Li, Fangfang; Zhao, Jing; He, Yu; Xiang, Shangtian; Zang, Weizhou (Frontiers in Immunology, 2025)
BackgroundPrimary angiitis of the central nervous system (PACNS) is a rare immune-mediated vasculitis with distinct subtypes (large/medium-vessel [LV-PACNS] and small-vessel [SV-PACNS]). This study aims to provide evidence-based data from the Chinese population for improving the subtype-specific management system of PACNS.MethodsThis retrospective single-center study enrolled 47 PACNS patients (29 with SV-PACNS, 18 with LV-PACNS) who met the 1988 Calabrese and Mallek diagnostic criteria, with a follow-up duration ≥1 year. Clinical phenotypes, imaging characteristics, treatment, prognosis, and factors influencing prognosis were retrospectively analyzed in both groups.ResultsCompared with LV-PACNS, SV-PACNS had more severe initial neurological impairment (baseline modified Rankin Scale mRS score: 3 vs. 2, p=0.043) and a longer median time from onset to treatment initiation (154 days vs. 58.5 days, p=0.013). In terms of clinical features, LV-PACNS had a higher incidence of cerebrovascular events (88.9% vs. 58.2%, p=0.027) and limb weakness/sensory abnormalities (83.3% vs. 34.5%, p=0.001), while SV-PACNS had a higher incidence of tumor-like lesions (41.4% vs. 5.6%, p=0.008). Imaging features showed that 100% of LV-PACNS patients had cerebrovascular stenosis, of which 94.4% exhibited circumferential vascular wall enhancement; and compared with SV-PACNS, they had a higher incidence of ischemic infarction (66.7% vs 20.7%, p=0.002). Multivariate analysis confirmed that time from onset to treatment was an independent risk factor for poor 1-year prognosis (mRS score > 2) in both subtypes (SV-PACNS: OR = 1.012, p=0.021; LV-PACNS: OR = 1.048, p=0.040).ConclusionsThis study identified the core clinical and neuroimaging differences between LV-PACNS and SV-PACNS, and pointed out that treatment delay are the main issues affecting prognosis.